Development Strategy to Improve Class Classification In Nusantara Fishery Port Pengambengan, Bali Province - Suyoga, I Gede; Restu, I Wayan; Negara, I Ketut Wija; Sudananjaya, Bagus (Advances in Tropical Biodiversity and Environmental Sciences, 2021)
In the framework of improving governance, functional dimensions, and performance of the fishing port, the Nusantara Fishery Port in Jembrana Bali compiles a "strategic plan" to improve the class classification of the Nusantara Fishing Port Pengambengan to become a class A Ocean Fishing Port, a number of management facility criteria are required as the main prerequisites. The purpose of this study was to determine the condition of the facilities at Nusantara Fishing Port Pengambengan and to determine the strategy for developing a fishing port at Nusantara Fishing Port Pengambengan. This research method uses descriptive qualitative and quantitative methods. Data collection techniques through direct observation and interviews using a questionnaire regarding the condition of the facilities at Nusantara Fishing Port Pengambengan, then data analysis using a SWOT analysis approach. Nusantara Pengambengan Fishery Port is a class B port that functions as a support for the management and utilization of fish resources and the environment, starting from pre-production, production, processing and marketing of fishery products. In supporting fishery activities, Nusantara Fishing Port Pengambengan is currently supported by various facilities, namely basic facilities, functional facilities, and supporting facilities. The results showed that there were several facilities in poor conditions, namely basic pier facilities, anchoring ponds, complex roads, and drainage, from supporting facilities, namely public toilets and guest houses. Several facilities are not available in the Nusantara Fishing Port Pengambengan construction, namely ship docks, net repair wards/places, laboratories, WWTPs, watchtowers, and perimeter fences. The strategies obtained from the results of this study include: (1) Improving the quality of the catch to provide a positive image for potential investors. (2) Improve administrative services to provide fishermen comfort when carrying out fishing operations. (3) Support is needed, especially the role of the government related to management and development.